BEYOND WORDS: BALANCING TOP-DOWN AND BOTTOM-UP SKILLS IN TASK-BASED LISTENING ASSESSMENT - Rakhimova Mardona Odilbek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: The article Beyond Words: Balancing Top-Down and Bottom-Up Skills  in  Task-Based  Listening  Assessment  examines  the  interplay  between  two essential dimensions of listening comprehension: bottom-up processing, which focuses on decoding linguistic elements such as sounds, vocabulary, and grammar, and top-down processing, which relies on background knowledge, prediction, and inference. It argues that listening assessment often emphasizes one skill at the expense of the other, leading to incomplete evaluations of learners’ proficiency. Through discussion of task-based  assessment  approaches,  the  article  highlights  how  authentic  tasks—such  as information-gap  activities,  problem-solving  discussions,  and  the  use  of  real-world audio  materials—can  integrate  both  micro-level  detail  recognition  and  macro-level understanding.  The  article  also  outlines  pedagogical  implications,  emphasizing authenticity, scaffolding, fairness, and meaningful feedback in assessment design. By advocating  for  a  balanced  framework,  the  work  contributes  to  current  debates  in applied  linguistics  and  assessment  design,  suggesting  that  effective  listening assessment  must  go  beyond  isolated  word  recognition  to  measure  holistic communicative competence.